2010
DOI: 10.1253/circj.cj-09-1028
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind and Placebo-Controlled Study of the Effectiveness and Safety of Extracorporeal Cardiac Shock Wave Therapy for Severe Angina Pectoris

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp he number of patients with severe angina pectoris without indications for coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) is rapidly increasing worldwide and their prognosis still remains poor. 1,2 Thus, it is crucial to develop new therapeutic strategies for these patients. We have previously demonstrated that extracorporeal cardiac shock wave (SW) therapy with low-energy SW (≈1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 14 publications
(18 reference statements)
7
90
0
1
Order By: Relevance
“…We have developed a non-invasive angiogenic therapy with extracorporeal low-energy shock waves (SW), and have demonstrated its efficacy and safety in a porcine model of chronic myocardial ischemia 7 and patients with angina pectoris. 8, 9 Furthermore, we have demonstrated that SW therapy ameliorates LV remodeling after AMI in pigs in vivo. 10, 11 However, it remains to be examined whether SW therapy also exerts anti-inflammatory effects on AMI in addition to its angiogenic effects.…”
Section: Methodsmentioning
confidence: 97%
“…We have developed a non-invasive angiogenic therapy with extracorporeal low-energy shock waves (SW), and have demonstrated its efficacy and safety in a porcine model of chronic myocardial ischemia 7 and patients with angina pectoris. 8, 9 Furthermore, we have demonstrated that SW therapy ameliorates LV remodeling after AMI in pigs in vivo. 10, 11 However, it remains to be examined whether SW therapy also exerts anti-inflammatory effects on AMI in addition to its angiogenic effects.…”
Section: Methodsmentioning
confidence: 97%
“…ESWT is an effective, safe, and non-invasive therapeutic strategy for severe coronary artery disease (Fukumoto et al, 2006;Khattab et al, 2007;Kikuchi et al, 2010;Vasyuk et al, 2010). In this study, we demonstrated that SW treatment up-regulates the expression of VEGF in HUVECs, leading to an increase in VEGF protein secretion.…”
Section: Discussionmentioning
confidence: 57%
“…Extracorporeal shock wave therapy (ESWT) has been recently introduced as a novel noninvasive option for the treatment of patients with severe coronary artery disease, such as angina pectoris, ischemic heart failure, and systolic dysfunction (Fukumoto et al, 2006;Khattab et al, 2007;Kikuchi et al, 2010;Vasyuk et al, 2010). ESWT has been shown to promote coronary angiogenesis in the ischemic myocardium and improve myocardial function in vivo in a porcine model of chronic myocardial ischemia (Nishida et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial blood flow and cardiac function were improved and enhanced VEGF production was observed in vitro and in vivo. The efficacy and safety of ESWT for patients with angina pectoris has also been reported (Fukumoto et al 2006;Kikuchi et al 2010). Moreover, Hayashi et al (2012) reported that endothelial nitric oxide synthase played a critical role in ESWT-induced accelerated wound healing in diabetic mice by promoting VEGF expression and neovascularization.…”
Section: Introductionmentioning
confidence: 86%